The Principal’s Role In Enhancing Student Achievement At The Bengkulu Province Sports Talent Senior High School - IS, Tuti Handayani; Lorita, Evi; Sariningsih, Marida; Sari, Rozi Anita (Utan Kayu Publishing, 2022)
This study aims to examine in depth the influence of principal leadership on student achievement in talent-based sports schools, emphasizing the framework of transformational leadership. The primary focus is to determine how the principal’s role contributes to creating a supportive learning environment, fostering students' intrinsic motivation, and cultivating a sustainable culture of excellence. A quantitative approach was employed using a simple linear regression model, supported by qualitative data from students’ open-ended responses. The findings revealed a significant impact of the principal’s role on student performance, with a coefficient of determination (R²) of 0.58 and a t-statistic value of 8.143 (p 0.05). This indicates that 58% of the variance in student achievement is attributable to the principal's leadership, while the remaining 42% is influenced by other factors such as training quality, parental involvement, and individual student conditions. Qualitative insights reinforce the statistical results, showing that students perceive the principal’s emotional support, personal attention, and active involvement in training and competitions as highly impactful. The principal is viewed not merely as an administrator, but as a motivator, facilitator, and central figure in the development of student achievement. The study underscores the importance of strengthening leadership competencies, especially in interpersonal communication, motivation strategies, and the cultivation of adaptive school environments. This research offers both practical and theoretical contributions to the development of effective educational leadership models in talent-based schools.